2007
DOI: 10.1002/j.2161-0045.2007.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Types of Workplace Social Support in the Prediction of Job Satisfaction

Abstract: Research on social support and job satisfaction has yielded mixed results, partly because studies have rarely examined different types of workplace social support, such as collegial support, task support, coaching, and career mentoring. This study identified the relative contributions of different types of social support to job satisfaction and explored the relationship between social support and job tenure. Overall, social support accounted for approximately 17% of the variance in job satisfaction and 9% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
1
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 25 publications
6
108
1
13
Order By: Relevance
“…This expectation was partly grounded on prior research; for instance, Harris, Winskowski, & Engdahl (2007) showed that workplace task support (conceptualized as a predictor) correlated with longer job tenure. In contrast, Creed & Moore (2006) found that unemployed individuals experienced a reduction in social support from significant others.…”
Section: Hypothesis 2a Employment Duration Is Positively Related To mentioning
confidence: 97%
“…This expectation was partly grounded on prior research; for instance, Harris, Winskowski, & Engdahl (2007) showed that workplace task support (conceptualized as a predictor) correlated with longer job tenure. In contrast, Creed & Moore (2006) found that unemployed individuals experienced a reduction in social support from significant others.…”
Section: Hypothesis 2a Employment Duration Is Positively Related To mentioning
confidence: 97%
“…Social support manifests between individuals who are usually members of the same network. Harris, Winskowski, and Engdahl (2007) reported that peer, supervisor, and family support can increase individuals' resistance to any obstacles that they might face and reduce anxiety and depression. Moreover, Sultan and Rashid (2015) suggest that social support can partially mediate the relationship between user satisfaction and perceived stress.…”
Section: Social Support Theorymentioning
confidence: 99%
“…Throughout the years, social support has played an important role in the social psychological literature in predicting the overall well-being of an individual. Research indicates that workplace social support is related to positive vocational outcomes, including reduced absenteeism and position turnover, increased resistance to burnout, and reduced depression and anxiety (Harris, Winskowski, & Engdahl, 2007). Social support can serve as a form of coping resource.…”
Section: Social Support Theorymentioning
confidence: 99%
“…Furthermore, supporters can decrease the distress employees suffer when faced with difficult situations by providing feedback which could be perceived as caring, understanding, or affirmative. Thus, research has found that workplace social support is positively related to greater job satisfaction and training effectiveness, and the level of social support received from significant others, including top management, supervisors, peers, and subordinates, all have an influence on individuals (Chen et al, 2007;Harris et al, 2007). In addition to the social support an employee perceives as having in his/her work environment, Adams, King, and King (1996) uncovered the fact that higher levels of family emotional and instrumental social support are significantly associated with less family and work conflicts, less workplace stress (Noor, 2002), and further believe that a higher level of job satisfaction (King et al, 1995) would be the result.…”
Section: Social Support Theorymentioning
confidence: 99%